The impact of psychological distress on problematic smartphone use among college students: The mediating role of metacognitions about smartphone use - Chen, Huohong; Ma, Jing; Guan, Jinliang; Yin, Lin; Shi, Zifu; Zhang, Yihan (Frontiers in Psychology, 2022)
A mediation model was constructed to clarify the relationship and mechanisms linking psychological distress to problematic smartphone use, focusing on the mediating role of metacognitions about smartphone use. A questionnaire method was used to investigate psychological distress, metacognitions about smartphone use, and problematic smartphone use among 664 college students. The results showed that (1) psychological distress had a significant positive predictive effect on problematic smartphone use, and (2) there were differences in the underlying mechanisms linking different types of psychological distress to problematic smartphone use. Specifically, negative metacognition about smartphone use partially mediated the relationship between depression and problematic smartphone use, whereas anxiety could act on problematic smartphone use through parallel mediation of positive metacognition about smartphone use and negative metacognition about smartphone use, with the latter having a greater positive mediating effect than the former. These findings reveal the mechanism of action linking different types of psychological distress to problematic smartphone use from the perspective of the cognitive-behavioral model of pathological Internet use, which has implications for the prevention and intervention into problematic smartphone use among college students.